Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1074/jbc.273.19.11498
|View full text |Cite
|
Sign up to set email alerts
|

pH-induced Conformational Transitions of the Propeptide of Human Cathepsin L

Abstract: Synthesis of proteases as inactive zymogens is a very important mechanism for the regulation of their activity. For lysosomal proteases proteolytic cleavage of the propeptide is triggered by the acidic pH. By using fluorescence, circular dichroism, and NMR spectroscopy, we show that upon decreasing the pH from 6.5 to 3 the propeptide of cathepsin L loses most of the tertiary structure, but almost none of the secondary structure is lost. Another partially structured intermediate, prone to aggregation, was ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
1
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 70 publications
5
77
1
4
Order By: Relevance
“…For cathepsin L, it was proposed that DS unfolds the tertiary structure of the propeptide at pH values below ϳ5.5, thereby increasing its susceptibility to proteolysis (65). However, no conformation changes of pro-cathepsin L during autoprocessing could be found by further studies (66), and similarly, we could not detect any major conformation changes during pro-TPP I autoactivation (25).…”
Section: Figcontrasting
confidence: 42%
“…For cathepsin L, it was proposed that DS unfolds the tertiary structure of the propeptide at pH values below ϳ5.5, thereby increasing its susceptibility to proteolysis (65). However, no conformation changes of pro-cathepsin L during autoprocessing could be found by further studies (66), and similarly, we could not detect any major conformation changes during pro-TPP I autoactivation (25).…”
Section: Figcontrasting
confidence: 42%
“…On the other hand, at pH 4, it lost a large part of its tertiary structure but retained its secondary structure content. 25 In these conditions, the obtained propeptide intermediate was able to bind ANS. Our data showed that, as for the cathepsin L propeptide, the Der p 1 propeptide and its C-truncated form were folded as compact globular domains at neutral pH.…”
Section: Free Propeptide Structure and Ph Unfoldingmentioning
confidence: 95%
“…21 For the cathepsin L propeptide, lack of inhibition has been associated with partial unfolding of the propeptide and formation of a molten globule state under acidic conditions. 25 Moreover, under these conditions, it has been demonstrated that the cathepsin S propeptide is slowly degraded by mature cathepsin L. 21 To date, the interaction between mature Der p 1 and its propeptide has not been investigated due to the difficulty of obtaining correctly matured recombinant Der p 1 (rDer p 1). In order to characterize this interaction, we studied the activation steps involved in the zymogen maturation mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the processing occurred in refolding buffer at an alkaline pH (8.0) at which mature falcipain-2 has minimal activity against peptide substrates or hemoglobin. For other papain family enzymes, acidic conditions appear to be required to unfold the prodomain and allow autoactivation (62). Processing of profalcipain-2 may have been expedited by the fact that our expression construct included a truncated prodomain.…”
Section: Falcipain-2 a P Falciparum Trophozoite Hemoglobinasementioning
confidence: 99%